Dry reforming of methane over Ni/ZrO2-Al2O3 catalysts: Effect of preparation methods - Shin, Seol A.; Noh, Young Su; Hong, Gi Hoon; Park, Ji In; Song, Hyun Tae; Lee, Kwan-Young; Moon, Dong Ju (Elsevier Science, 2018)
Ni/ZrO2-Al2O3 catalysts were prepared by different methods such as modified Pechini sol-gel, urea hydrolysis, and physical mixing, and were evaluated by the dry reforming of methane under the conditions of reaction temperature of 700 degrees C, an atmospheric pressure, and a space velocity of 25,000 h(-1). It was established that the interaction between nickel and support in the dry reforming of methane depends on the preparation methods of catalyst, and plays an important role in terms of the resistance to carbon formation. From the results, we suggested that the Ni/ZrO2-Al2O3 catalyst prepared by Pechini sol-gel showed higher stability under the tested reaction conditions. These results are interpreted that the interaction between nickel and ZrO2-Al2O3 promotes the dissociation of CO2. It was considered that the catalytic stability in the dry reforming of methane over Ni/ZrO2-Al2O3 catalyst was maintained by the balance for the reaction of deposited carbon and oxygen intermediate derived from the dehydrogenation of methane and the dissociation of CO2. The results are concluded that the Ni/ZrO2-Al2O3 (PS) catalyst is a desirable catalyst with the resistance to carbon formation in the dry reforming of methane. (C) 2017 Taiwan Institute of Chemical Engineers. Published by Elsevier B.V. All rights reserved.